Only a matter of time? The role of time in school on four-day school week achievement impacts. (February 2022) - Thompson, Paul N.; Ward, Jason
Abstract: Previous evidence has shown disparate achievement impacts of the four-day school week within specific states. This paper examines the effects of the four-day school week on achievement across 12 states to contextualize these four-day school week impacts nationally. We estimate these effects using a difference-in-differences design with data from the Stanford Educational Data Archive and a proprietary longitudinal national database of four-day school week use from 2009 to 2018. We find reductions in both math and English/language arts achievement when examining four-day school weeks nationally, but these aggregate effects appear to be masking important heterogeneity due to differences in overall time in school across districts. When stratifying four-day week districts into districts with low, middle, and high levels of time in school, we find statistically significant negative effects on math achievement for four-day school week districts with low time in school, but no statistically significant effects for four-day school week districts with middle or high time in school. Our findings suggest that maintaining sufficient overall time in school should be a key consideration for school districts contemplating four-day school week adoption.